Development of Augmented Reality Book to Improve IPAS Learning Outcomes - Armia, Naja Izza; Andriani, Aldina Eka (Jurnal Pijar Mipa, 2025)
Teachers have not been optimal in using technology-based teaching materials, causing the learning outcomes of fourth-grade students of Purwoyoso 04 State Elementary School in Semarang City on IPAS subjects, especially photosynthesis material, to be low. This study aims to describe the development design, test the feasibility, and effectiveness of the Augmented Reality Book to improve student learning outcomes. This type of research is Research and Development (R&D) with the Borg and Gall model. Data were collected through tests (pre-test and post-test) and non-tests (observation, interview, and questionnaire), then analyzed using a normality test, t-test, and N-gain. The results showed that the development design using Assemblr Edu and Canva applications produced an interactive and innovative Augmented Reality Book with components of instructions for use, CP and TP, concept maps, Problem-Based Learning-based materials, 3D content, interactive learning videos, student worksheets, and quizzes. The feasibility of the product from material experts is 92.5% and material experts are 89% very feasible criteria, supported by the results of the analysis of teacher and student response questionnaires of 100% very feasible criteria. The effectiveness of the product is shown by an increase in pre-test and post-test by 22%, supported by a t-test showing the value of Sig. (2-tailed)=0.001< 0.05, which means there is a significant difference between learning outcomes before and after using the product, as well as an N-gain score of 0.64 in the medium category. The conclusion of this study shows that the Augmented Reality Book was successfully developed, feasible and effective in improving learning outcomes of photosynthesis material in IPAS learning class IV SD Negeri Purwoyoso 04 Semarang City.